Proinflammatory Matrix Metalloproteinase-1 Associates With Mitral Valve Leaflet Disruption Following Percutaneous Mitral Valvuloplasty - Passos, Livia S. A.; Becker-Greene, Dakota; Braulio, Renato; Le, Thanh-Dat; Gelape, Cláudio L.; de Almeida, Luís Felipe R.; Rocha, Divino Pedro A.; Gomes, Carlos Augusto P.; Esteves, William A. M.; Passaglia, Luiz G.; Dal-Bianco, Jacob P.; Levine, Robert A.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Mitral regurgitation (MR) is a major complication of the percutaneous mitral valvuloplasty (PMV). Despite high technical expertise and cumulative experience with the procedure, the incidence rate of severe MR has not decreased. Although some of MR can be anticipated by echocardiographic analysis; leaflet tearing, which leads to the most dreaded type of MR, remains unpredictable. Irregular valvular collagen remodeling is likely to compromise tissue architecture and increase the tearing risk during PMV balloon inflation. In this study, we evaluated histological and molecular characteristics of excised mitral valves from patients with rheumatic mitral stenosis (MS) who underwent emergency surgery after PMV due to severe MR caused by leaflet tear. Those findings were compared with patients who underwent elective mitral valve replacement surgery owing to severe MS, in whom PMV was not indicated. In vitro assay using peripheral blood mononuclear cells was performed to better understand the impact of the cellular and molecular alterations identified in leaflet tear mitral valve specimens. Our analysis showed that focal infiltration of inflammatory cells contributes to accumulation of MMP-1 and IFN-γ in valve leaflets. Moreover, we showed that IFN-γ increase the expression of MMP-1 in CD14+ cells (monocytes) in vitro. Thus, inflammatory cells contribute to unevenly remodel collagen resulting in variable thickening causing abnormalities in leaflet architecture making them more susceptible to laceration.